Reduksi Tingkat Kebisingan Kendaraan Bermotor Dengan Penghalang Alami Berupa Panjang Klaster Tanaman - Jumingin, Jumingin; Atina, Atina (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2019)
Research on motor vehicle noise reduction has been carried out with natural barriers in the form of plant cluster lengths. The purpose of this study was to determine the effect of plant cluster length as a natural barrier to reduce motor vehicle noise levels. This study uses a purposive sampling method, where in the study of noise level measurements carried out at selected points and determined in accordance with existing plant clusters at the study site. The tools used in this study are sound level meter, stopwatch, roll meter and tripod. Sound level meters are placed in front of plant clusters and behind plant clusters at a height of 120cm above ground level. The noise level in front of and behind the planting cluster is measured simultaneously for 30 days during the daytime measurement activity. The data obtained were analyzed using one factorial variance analysis in the form of plant cluster length. The results showed that the noise reduction by the cluster of cape, bungur, Tembesi, mahogany and palm clusters with a cluster length of 25m was 10.5 dB; 8,6dB; 9,1dB; 5,4dB and 5,2dB, the length of the 20m plant cluster is 9.5 dB; 7.5dB; 6,4dB; 4.0 dB and 4.4 dB, the plant cluster length of 17.5 m is 5.9 dB; 5,8dB; 5,1dB; 3,4dB and 3,8dB, the length of the 15m plant cluster is 4.2 dB; 3,5dB; 3,9dB; 2,9dB and 3,1dB, the length of the 10m plant cluster is 3,8dB; 3,3dB; 2,7dB; 2,3dB and 2,7dB, and the 7.5m plant cluster length is 3,08dB; 3,1dB; 1,6dB; 1.7dB and 1.8dB. From BNT test with 99% confidence level showed that the greater difference in plant cluster length has a very significant effect on noise level reduction.